Translation through Visualization - Kußmaul, Paul (Meta, 2005)
AbstractThere are many aspect of professional translation. Problem solving is certainly one of them, and visualization has occasionally been recommended in this context. In this article, think aloud protocols (dialogue protocols) are analysed with the aim of observing instances of visualizations that lead to successful translations. As a heuristic means cognitive notions (prototypes, scenes and frames and focus) are used. In general, it seems that visualizing details of a scene helps translators to arrive at creative translations.